Η ποικιλομορφία και η πολυλειτουργικότητα του ρατσισμού σε άρθρα μεταναστευτικής εφημερίδας - Αρχάκης Αργύρης; Τσάκωνα Βίλλυ (Παιδαγωγικά ρεύματα στο Αιγαίο, 2024)
Contemporary western nation-states are built on national and racist discourses and values which are not easily contested by majority members and may affect the discourse and behaviors of minority members as well, even though the latter suffer from the discriminatory consequences of such discourses and values. Research has shown that minority members do not always resist national/racist pressures but often succumb to them, thus accepting majority values and perceiving themselves as Others, namely as majority members usually perceive them. In this context, the present study attempts to explore ways of detecting minority members’ (in the present case, migrants’) internalized racism (Pyke, 2010). The critical analyses performed on two newspaper articles written by young female migrants living in Greece aim to show that, in their effort to adjust themselves to the Greek linguacultural context and to form ties with majority members, the authors reproduce racist views and values usually attested among members of the Greek majority. Given that these articles are published in a newspaper of left wing, antiracist, and pro-migrant orientation, the co-existence of racist and antiracist meanings and values in the same texts blurs the boundaries between racism and antiracism. This renders the texts examined here instances of liquid racism (Weaver, 2016), namely an ambiguous form of racism giving rise to opposing (i.e. racist and antiracist) interpretations and further entrenching the hegemony of racist discourse.